Optimalisasi Peran Kader Kesehatan dalam Edukasi dan Implementasi Gaya Hidup Sehat Lansia - Sundari Indah Wiyasihati; Hayuris Kinandita Setiawan; Purwo Sri Rejeki; Lilik Herawati (Warta LPM, 2023)
The health problems of the elderly in ​​the Puskesmas Industri, Gresik work area align with the Indonesian health phenomenon where the number of elderly and degenerative diseases is high. Health cadres training in the work area of ​​the Puskesmas Industri is needed to optimize the role of cadres in educating and implementing a healthy lifestyle in older adults. The Community Partnership Program, focusing on health as part of goal 3 of The Sustainable Development Goals (SDGs), was carried out on September 1, 2022, and was attended by 57 cadres from 6 villages. Health information was provided as a provision for cadres to provide education to the public about the healthy lifestyle of the elderly. The results showed that there was an increase of 17,26 points (34,76%) after training. The lowest post-test results were on the topic of BMI and its interpretation, as well as physical activity in the elderly, so further action is needed. During FGD, the Elderly Health Book from the Ministry of Health of the Republic of Indonesia was introduced. The results of the FGD showed that the introduction of the Elderly Health Book should be continued so that health cadres can consistently use it. Health cadres have a significant role in realizing the elderly health program from the Indonesian Ministry of Health. This health cadre training has proven to be very necessary because it can increase understanding as a provision for cadres in providing education to the public regarding the healthy lifestyle of the elderly.